Capacities strengthening on Climate-Smart Agriculture (CSA): Good practices and illustrative examples during field visits in Ghana - Akponikpè, Pierre B.I.; Zakari, Sissou; Gibrilla, Ahmed; Kpadonou, G. Esaïe; Adjogboto, André; Orou Barre Fousseni, Imorou; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2024)
As part of the series of capacity building of stakeholders at national and local levels on Climate Smart Agriculture (CSA) in five West African countries (Benin, Burkina Faso, Ghana, Niger, and Togo), field visits were organized to illustrate classroom theoretical learning with practical examples on the ground in each country. This report presents good practices and illustrative examples during field visits in Ghana. The capacity building series was implemented as part of the Regional Project for the Promotion of Climate-Smart Agriculture (CSA) in West Africa (AIC-BOAD) by the Alliance Bioversity International and CIAT, in partnership with the Regional Agency for Agriculture and Food (RAAF/ECOWAS), the project coordination and implementation entity, and the National Project Management Units (UNGP) in each country.